What Happens When Policies Are Transferred? The Privatisation Of The Telephone Organisation Of Thailand - Chulajata, Issariyaporn; Turner, Mark (Penerbit Universiti Sains Malaysia (USM Press), 2009)
There is considerable interest in how policies originating in one time or place are adopted in other places and times. Explanations of this phenomenon have been dominated by three approaches: policy diffusion, policy convergence and policy transfer. This article demonstrates that each approach has both strengths and weaknesses, and no approach can, on its own, does adequate explanatory justice to the complexity of policy transfer from rich to poor countries. The article uses the case of the transfer of telecommunications privatisation policy to Thailand to show this complexity and focuses on the Telephone Organisation of Thailand (TOT). The case is presented to support the argument that the interaction of domestic and international actors among the unique structural features and historical events of a particular place result in the modification of policies as they move between countries and after they have arrived at their new destination.